The Philosophy and Semantics of the Cognitive Science of Religion - Gardiner, Mark Q. (Journal for the cognitive science of religion, 2015)
This article brings philosophy into dialogue with cognitive science of religion (CSR). After a brief overview of CSR and theories of meaning, we explore the philosophical semantic constraints of CSR. We focus on how the beliefs and behaviours of religious adherents, as conceived by CSR, can be meaningful in ways that illuminate the scholar's understanding of religious phenomena. We argue that CSR is committed to an externalist and holistic semantics. This highlights a potentially problematic tension between the beliefs of religious people and the explanations proposed by CSR. We end by suggesting that this tension could be resolved if CSR were to give more attention to external factors (e.g., biological, cultural, environmental etc.).